2021
DOI: 10.1038/s41420-021-00711-w
|View full text |Cite
|
Sign up to set email alerts
|

Role of RAGE in obesity-induced adipose tissue inflammation and insulin resistance

Abstract: AbatractObesity is known to be associated with adipose tissue inflammation and insulin resistance. Importantly, in obesity, the accumulation of proinflammatory macrophages in adipose tissue correlates with insulin resistance. We hypothesized that the receptor for advanced glycation end products (RAGE) and associated ligands are involved in adipose tissue insulin resistance, and that the activation of the AGE–RAGE axis plays an important role in obesity-associated inflammation. C57BL/6J mice (WT) and RAGE defic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0
1

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 27 publications
1
26
0
1
Order By: Relevance
“…The limitation of the clinical design of the study is that we could not compare the GA and MGO values in a control group matched for obesity and the prevalence of diabetes. However, the interpretation of the data that we are supporting here is greatly supported by the large epidemiological studies on COVID-29 syndrome that found a highly significant association of obesity and diabetes with the severity of SARS-CoV-2 infection [ 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 ].…”
Section: Discussionsupporting
confidence: 75%
See 2 more Smart Citations
“…The limitation of the clinical design of the study is that we could not compare the GA and MGO values in a control group matched for obesity and the prevalence of diabetes. However, the interpretation of the data that we are supporting here is greatly supported by the large epidemiological studies on COVID-29 syndrome that found a highly significant association of obesity and diabetes with the severity of SARS-CoV-2 infection [ 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 ].…”
Section: Discussionsupporting
confidence: 75%
“…It is also of interest that MGO-induced RAGEs play a role in platelet activation [ 14 ], which may lead to additional SARS-CoV-2 infection complications. These metabolic processes are also expressed in control pregnant subjects since pregnancy is characterized by para-physiological dyslipidemia and insulin resistance [ 7 , 15 , 16 ]. This could explain why, even in otherwise clinically normal pregnancies, we observed a wide range of GA and MGO values.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent evidence suggests a receptor for advanced glycation end-products (RAGE) mediated mechanism of OXT transport to the brain [ 34 ]. Obesity is known to increase expression of RAGE [ 35 , 36 ], and it is possible that in our DIO Sprague Dawley rats increased transport which needs to be investigated for ASK2131 vs. OXT in a future study.…”
Section: Discussionmentioning
confidence: 99%
“…The 8-week-old male C57BL/6J mice were fed with a HFD (fat 60%, carbohydrate 25% and protein 15%) for 16 weeks, as described previously [33,34]. Age-matched male mice fed with a normal chow diet (fat 10%, carbohydrate 75% and protein 15%) were used as controls.…”
Section: Hfd-fed Mouse Modelmentioning
confidence: 99%